The Mediator Roles Of Attitude Toward The Web Site And User Satisfaction On The Effect Of System Quality On Net Benefit: A Structural Equation Model On Web Site Success - Civelek, Mustafa Emre; İnce, Hüseyin and Karabulut, Ahu Tuğba (European Scientific Journal, ESJ, 2016)
The purpose of this study is to examine the mediator roles of attitude toward the web site and user satisfaction on the effect of system quality on net benefit. A new conceptual model for web site success is developed based on previous models in the literature. System quality is one of the most important antecedent of perception of net benefit for customers of B2C sites. The effect of system quality on net benefit has been through user satisfaction in the literature. Some models included attitude toward the web site dimension in the same level with user satisfaction. Therefore, the research model suggested these two variables play mediator roles on the effect of system quality on net benefit. A structural equation model is used to analyze this model. It is statistically proved that attitude toward the web site and user satisfaction play mediator roles on the effect of system quality on net benefit.